The Re-emergence of African Spiritualities: Prospects and Challenges. (October 2019) - Nweke, Kizito Chinedu; Okpaleke, Ikenna Paschal
Indigenous spiritualities among Africans, both in Africa and in the diaspora, are flourishing. In Lagos, Nigeria, for example, shrines compete with churches and mosques in adherents and positions. Beyond Africa, the rise of African spiritualities has become conspicuous. Reasons range from Afrocentrism to anti-religious tendencies to the popular religions, from racial animosity to politico-economic ideologies, yet insufficient attention is being paid to this new Afro-spiritualities. Can this renaissance in African spirituality bring forth or support a renaissance in Africa? Africa arguably domesticates the future of humanity. From ecological perspectives to the productivity of offspring, from economic potentials to viable youths for the future, Africa must become progressively discursive in the global platform. A good way to indulge in this would be to understand the spirit of Africa, in the traditional spiritualities that constructed orientations and worldviews of the people. Understanding and addressing African spiritualities constitute an important key in understanding the African identity.